Mediation and thinking development in schools : theories and practices for education : theories and practices for educators - Flavian, Heidi (Emerald points., 2019)
The benefits of mediation upon the development of children is an area that is yet to be fully explored. Mediation promotes learning through learner interactions with the environment and puts emphasis on the idea that society is responsible for all children's development.This book offers a unique practical model of effective mediation that integrates mediation theories from different periods and draws upon the work of five theoreticians; Dewey, Piaget, Vygotsky, Feuerstein, and Gardner. Key results from more recent neuropedagogical research are also presented. Mediation and Thinking Development in Schools supports the idea that academic achievements are not enough to measure a child's development; forward-thinking educators know that they not only have to teach specific disciplinary content, but also knowledge and skills that will be useful in their students' future. Hence, there is a need to understand how to mediate knowledge acquisition rather than be the source of knowledge. By fully illuminating the theory and the practice of mediation, this important text will prove invaluable for leaders, researchers and teachers in primary and secondary education.